Integral representations of solutions of the heat equation - Djrbashian, A. E. (Հայաստանի ԳԱԱ)
The paper defines new classes of solutions of the heat equation in half-spaces and presents a series of integral representations for them. On the basis of these formulas boundedness of corresponding integral operators is proved.
Keywords: Mathematics; Science